STRATEGI BERTAHAN HIDUP JANDA USIA MUDA DI KOTA PALOPO - Ismail Ismail; Muhammad Ashabul Kahfi; Ahmad Sufyan Tsauri; Bahtiar Bahtiar; Fitriani Jamaluddin (AN-NISA, 2025)
The status of being a widow, especially for young women, often brings negative impacts on their daily lives. Therefore, this research aims to understand the obstacles faced by young widows and the strategies they employ to cope with these challenges. The study was conducted in Pontap Subdistrict, Palopo City, focusing on informants who have experienced divorce or the loss of their husbands within the age range of 19-40 years. The research employed a qualitative approach with the goal of providing an in-depth description of the cases under investigation. The findings of the research reveal that young widows in Pontap Subdistrict face primary challenges in the form of negative social stigma from the surrounding community and economic constraints. This stigma manifests as negative labels attached to the widow status, creating additional barriers in their daily lives. Meanwhile, economic constraints emerge as a crucial factor affecting their ability to meet the basic needs of their households. To address these challenges, young widows employ various strategies that can be categorized into active, passive, and networking strategies. Active strategies involve additional efforts, such as increasing working hours during leisure time. Passive strategies include measures like cutting down on expenses. Networking strategies involve more intensive involvement in community life, building close relationships with family members, neighbors, and relatives as a form of social support and fostering a sense of communal cooperation.